1998
DOI: 10.1021/om9708586
|View full text |Cite
|
Sign up to set email alerts
|

Organic Syntheses via Transition Metal Complexes. 95.1 Rearrangement of (Cyclobutenyl)carbene Tungsten Complexes to 1-Tungsta-1,3,5-hexatrienes

Abstract: (Cyclobutenyl)carbene tungsten complexes are shown to rearrange to 1-tungsta-1,3,5-hexatrienes. Azabicyclo[4.2.0]octadiene (bis)carbene tungsten complexes 3a − c, which served as model compounds in these studies, were generated by [4 + 2]- and [2 + 2] domino cycloaddition of 2 equiv of (1-alkynyl)carbene complex (CO)5WC(OEt)C⋮CPh (1) to alkenyl imidates RCHCHC(OEt)NR1 (2a − c) (R = Ph, Me; R1 = Me, i-Pr). Compounds 3 are stable in the solid state at 20 °C but rearrange in solution to 1-metalla-1,3,5-hexatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…[9] Compounds 12 exhibit spectroscopic features typical of (4-oxycyclobutenyl)carbene tungsten complexes. [14,15] Most notably, the 13 C NMR shift of the WϭC unit is observed in the range characteristic of nonconjugated 1-tungsta-1,3,5-hexatrienes, e.g. 12a: δ ϭ 319.4, thus indicating an apparently strong distortion of the (WϭC)-(CϭC) unit (which was indeed confirmed by the crystal structure analysis of compound 12b) and consequently little π-conjugation.…”
Section: 3-dioxytetrahydropentalenes and (Cyclobutenyl)carbene Tungsupporting
confidence: 52%
“…[9] Compounds 12 exhibit spectroscopic features typical of (4-oxycyclobutenyl)carbene tungsten complexes. [14,15] Most notably, the 13 C NMR shift of the WϭC unit is observed in the range characteristic of nonconjugated 1-tungsta-1,3,5-hexatrienes, e.g. 12a: δ ϭ 319.4, thus indicating an apparently strong distortion of the (WϭC)-(CϭC) unit (which was indeed confirmed by the crystal structure analysis of compound 12b) and consequently little π-conjugation.…”
Section: 3-dioxytetrahydropentalenes and (Cyclobutenyl)carbene Tungsupporting
confidence: 52%
“…Probing into the formation mechanism of a Fischer biscarbene complex and reactivity of the M@C bonds in it are two major aspects in exploration of Fischer biscarbene chemistry. In a previous paper co-authored by Aumann and Yu (one of the authors of this paper), et al [6], it was reported that reactions of 1-alkynyl Fischer carbene complexes (OC) 5 W (b)) with O-methyl lactims $(CH 2 ) n -N@C(OCH 3 )$ (n = 3, 4) afforded biscarbene complexes of type 3 (Scheme 1), in which the stability of a tungsten biscarbene complex over silica gel was studied, while further investigation of its chromium analogues failed due to complicated transformations of the chromium biscarbene complex under the same conditions. Thus, a more detailed and controlled study has been expected to probe into the formation and reactivity of complexes of type 3.…”
Section: Introductionmentioning
confidence: 81%
“…Rearrangement of a tungsten biscarbene complex of type 3 occurred over silica gel to give compound of type 4 in 21% yield [6], and isomerization of another tungsten biscarbene complex was also observed [5]. The chromium biscarbene complex, i.e., 3a, was applied for a comparison study with its tungsten analogue [6].…”
Section: Rearrangement Of Chromium Biscarbene Complex 3amentioning
confidence: 99%
See 1 more Smart Citation
“…The first type of Aumann's biscarbene complexes are not stable and decomposed by water, and the second are rearranged to ring-opened isomers on silica gel during column chromatography. 13,14 Alkenyl oxazolines excluding 2 were reported as achiral substrates for cyclopropanation with 1-alkenyl and 1-alkyl chromium Fischer carbene complexes. 15 Keeping in mind the structural similarity between alkenyl imidates and 2, we studied the reactions of 1 and 2.…”
Section: Introductionmentioning
confidence: 99%